Mechanical thrombectomy with intra-arterial alteplase provided better functional outcomes for AIS-LVO: a meta-analysis - Yang, Xingyu; Wang, Zilan; Chen, Huiru; Qiu, Youjia; Teng, Haiying; Chen, Zhouqing; Wang, Zhong; Chen, Gang (Frontiers in Neuroscience, 2023)
Background: Several clinical trials have shown that intra-arterial thrombolysis using alteplase during mechanical thrombectomy (MT) has a better outcome than MT alone in ischemic stroke management.We performed the current meta-analysis to estimate the efficacy and safety of MT with intra-arterial alteplase therapy.The MEDLINE, Embase, Cochrane Library , and ClinicalTrials.gov databases were searched up to Mar. 2022 to identify the clinical trials that compared MT alone versus MT with intra-arterial alteplase therapy. STATA 16.0 was used for statistical analysis. The odds ratios (ORs) and 95% confidence intervals (95%CIs) were calculated with a random effect model.Seven studies involving 1083 participants were included. The primary outcomes were better functional outcomes, defined as a modified Rankin Scale (mRS) score between 0 and 2 at 90 days, and successful recanalization, defined as a modified thrombolysis in cerebral infarction (mTICI) score ≥2b.Compared to MT alone, MT with intra-arterial alteplase did not lead to higher mTICI scores(OR 1.58, 95%CI 0.94 to 2.67, P=0.085, I 2 =16.8%) but did lead to better mRS (OR 1.37, 95%CI 1.01 to 1.86, P=0.044). There was no increase in mortality or bleeding events in the overall or subgroup analyses.MT with intra-arterial alteplase did not improve the recanalization rate but provided better functional outcomes. The intervention did not increase adverse effects in any subgroup at the same time.